Management Analysis of Tied Infaq and Sadaqah on the Tahfidz Quran Scholarship Program (Study of Yakesma Branch in Riau Islands) - Dasrizal, Fahmi; Aini, Nur (Jurnal Multidisiplin Madani, 2024)
The challenges faced in the management of Islamic philanthropic institutions include the potential for large infaq and sadaqah and the importance of infaq and sadaqah for the purpose of community empowerment, the dominance of the distribution of funds that are still consumptive so that they still do not empower the community, and the lack of accountability reporting to donors which can reduce their level of trust in Islamic philanthropic institutions. This research is important to gain an in-depth understanding of the effective management of tied infaq and alms through the Tahfidz Quran scholarship program, improve the effectiveness and efficiency of the management of tied infaq and alms funds, and provide recommendations for improving accountability and developing tied infaq and alms-based programs. This qualitative research with a case study approach analyzes the management of tied infaq and sadaqah in the Tahfidz Quran scholarship program run at the national amil zakat institution, YAKESMA Riau Islands Branch. Research data were obtained through interviews, field observations, and documentation studies related to the management carried out. The data was then analyzed descriptively by triangulating to ensure data validity and credibility. The theoretical framework of management, the concept of infaq and sadaqah, and SWOT analysis were used to interpret the factual findings comprehensively. The results show that efforts to overcome existing problems are expected to increase the effectiveness and accountability of the management of tied infaq and sadaqah funds and the management of Islamic philanthropic institutions in supporting programs with various other empowerment goals in the future